Neutrino signals of core-collapse supernovae in underground detectors. Issue 4 (8th August 2018) - Seadrow, Shaquann; Burrows, Adam; Vartanyan, David; Radice, David; Skinner, M Aaron
ABSTRACT: For a suite of 14 core-collapse models during the dynamical first second after bounce, we calculate the detailed neutrino 'light' curves expected in the underground neutrino observatories Super-Kamiokande, DUNE, JUNO, and IceCube. These results are given as a function of neutrino-oscillation modality (normal or inverted hierarchy) and progenitor mass (specifically, post-bounce accretion history), and illuminate the differences between the light curves for 1D (spherical) models that don't explode with the corresponding 2D (axisymmetric) models that do. We are able to identify clear signatures of explosion (or non-explosion), the post-bounce accretion phase, and the accretion of the silicon/oxygen interface. In addition, we are able to estimate the supernova detection ranges for various physical diagnostics and the distances out to which various temporal features embedded in the light curves might be discerned. We find that the progenitor mass density profile and supernova dynamics during the dynamical explosion stage should be identifiable for a supernova throughout most of the Galaxy in all the facilities studied and that detection by any one of them, but in particular more than one in concert, will speak volumes about the internal dynamics of supernovae.